Dobutamine stress echocardiography-induced Takotsubo cardiomyopathy. Which triggers?. (14th October 2021) - Meimoun, P; De Zuttere, D; Kasongo, A; Lardoux, H
Abstract: Aims: Takotsubo cardiomyopathy (TTC) is a rare complication of dobutamine stress echocardiography (DSE), a non-invasive modality widely used to detect myocardial ischemia. Purpose: Identification of clinical reports of TTC induced during DSE (TTC-DSE), and comparison to a selected group DSE exams group, with the objective to identify factors which could induce TTC during DSE. Methods: From an exhaustive search and review, using key words "apical ballooning, stress cardiomyopathy and DSE", 30 observations of DSE-TTC (2006–2020), with typical features of TTC were identified: (a) occurrence of TTC during DSE, (b) "InterTAK diagnostic criteria". Over a 3-year retrospective period (2013–2015), 578 consecutive DSE patients were selected and then compared to the TTC-DSE cohort. Results: The TTC-DSE cohort showed typical characteristics of TTC: strong predominance of aged female population >50 years (93.3%); depression and/or anxiety (26.7%); EKG: ST elevation (70%); normal coronary angiography; depressed angiographic left ventricular ejection fraction <40% (14/18 pts); typical segmental LV impairment: apical (7.3%); mid-ventricular (13.6%); reverse (9%); low troponin peak: 2.65±2.04 ng/ml; one death (acute heart failure), but rapid recovery of LVEF (29/30 pts) in few days. On the other hand, the DSE group of 578 consecutive patients showed: mean age 70 years (62–77 interquartile range), 44% of women, and frequent cardiovascular factors, diabetes (43%), hypertensive (41.4%) and dyslipidemia (28%). Significant differences with the TTC-DSE cohort were: mean age (70 vs 64), smoking (16 vs 36.6%), peak heart rate (94 vs 81%) and peak dose dobutamine (30 vs 40 μg/kg/mn), all p<0.01. In a multivariate analysis, female sex (OR=9.6; 95% CI: 3–28: p<0.01), smoking habit (OR=4.8; 95% CI: 2–11; p<0.01) and dobutamine dosage >30 μg/kg/mn (OR=1.07; 95% CI: 1.02–1.12; p<0.01) were independent predictors of DSE-TTC. Using ROC curve analysis, dobutamine dosage >30 μg/kg/mn gives the best cut off (AUC 0.7±0.04; p<0.01). Conclusion: TTC-DSE is a rare and severe situation, superimposable to the usual TTC. It gives the rare opportunity to observe TTC in its acute phase. By comparison to DSE patients, independent factors (female sex, smoking habit, dobutamine dosage >30 μg/kg/mn) are predictive of TTC-DSE. However, the discrepancy between the volume of daily DSE exams and the scarcity of TTC-DSE, remains poorly explained. FUNDunding Acknowledgement: Type of funding sources: None.